2020
DOI: 10.3390/ijerph17145059
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health and Work Attitudes among People Resuming Work during the COVID-19 Pandemic: A Cross-Sectional Study in China

Abstract: The unprecedented outbreak of the Coronavirus Disease 2019 (COVID-19) caused an economic downturn and increased the unemployment rate in China. In this context, employees face health and social economic stressors. To assess their mental health (i.e., anxiety, depression, insomnia and somatization) and work attitudes (i.e., work engagement, job satisfaction and turnover intention) as well as the associated factors, we conducted a cross-sectional study among people who resumed work after the Spring Festival holi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
102
2
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(118 citation statements)
references
References 58 publications
(89 reference statements)
7
102
2
7
Order By: Relevance
“…Symptoms as distress [ 12 , 13 , 16 ] and decreased appetite or indigestion are also frequently reported [ 12 ]. Our results are also in line with negative professional symptoms as stopping with the present job [ 15 , 22 ]. COVID-19-related studies showed that the prevalence in nurses for probable anxiety and depression was higher compared to doctors.…”
Section: Discussionsupporting
confidence: 88%
“…Symptoms as distress [ 12 , 13 , 16 ] and decreased appetite or indigestion are also frequently reported [ 12 ]. Our results are also in line with negative professional symptoms as stopping with the present job [ 15 , 22 ]. COVID-19-related studies showed that the prevalence in nurses for probable anxiety and depression was higher compared to doctors.…”
Section: Discussionsupporting
confidence: 88%
“…The last column describes the country or countries focus of the survey and/or the location of the participants. Category Subcategory Sample size Country and Reference Health and wellbeing indicators Mental Health and wellbeing Italy [158] , 59 countries [159] Bangladesh [160] , China [161] , [162] , USA [163] , [164] , [165] , Serbia [166] Canada [167] , China [168] , Ghana [169] , Jordan [170] , Italy [171] , Russia and Belarus [26] , USA [172] , [173] , [174] USA [175] Netherlands [176] Health Behaviors China [177] , Spain …”
Section: Surveysmentioning
confidence: 99%
“…It interesting to notice the variety of angles and aspects covered in the surveys on mental health. In fact, they consider loneliness [164] , [172] , [174] , domestic abuse [170] , psychological mindset [26] , [158] , [159] , [160] , [163] , [165] , [166] , [168] , [169] , as well as particular groups of the population studying the toll on frontline workers [161] , students [173] , [175] , parents and children [162] , [167] , [171] , [176] . Several common themes as well as some conflicting results emerged from this research.…”
Section: Surveysmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on the mental health implications of the COVID-19 pandemic is rapidly growing. However, relatively little academic work has attempted to identify dispositional protective factors against negative affective state during the pandemic ( 39 ). Previous research has identified a clear link between MT and resilience to stress, however, prior to this paper the relationship had not be explored in the context of the COVID-19 pandemic – a period of global and societal distress.…”
Section: Introductionmentioning
confidence: 99%